Evaporation and crystallisation of saline droplet with surfactant on smooth surfaces - Wong, Dennis Kin Wai (Nanyang Technological University, 2023)
The evaporation and crystallisation of saline droplets have attracted significant interest due to their potential applications in pharmaceutical production and medical diagnosis. Achieving precise control over droplet deposition is crucial in these fields, and the addition of surfactants can significantly affect the spreading and evaporation rates of droplets as well as the deposition of particles in the solution. While numerous studies have investigated the impact of surfactants on liquid droplets, very little research has been conducted on surfactants with opposing charges mixed with salt solutions. This project aims to examine the evaporative dynamics and crystallisation patterns of surfactant saline solutions. Specifically, a fixed concentration of Sodium Chloride (NaCl) solution will be mixed with two types of surfactants, Cetyltrimethylammonium bromide (CTAB) and Sodium dodecyl sulfate (SDS), at varying concentrations. The resulting droplets will be deposited on both hydrophilic silicon wafer and hydrophobic ITO glass surfaces. Results showed that as the concentration of CTAB increased, droplet spreading rate increased, and thicker dendrites were observed. Conversely, low concentrations of both CTAB and SDS mixed with NaCl resulted in droplet depinning on both substrates. The solutions that decreased in diameter did not maintain a constant circular shape during the retraction process, resulting in an irregular and distorted shape. In addition, the distribution of crystals varied with surfactants concentrations. At a high concentration of SDS (6.4 mM SDS), crystals were evenly distributed. On the other hand, at lower concentrations (0.32 mM SDS and 1.6 mM SDS), crystals were formed near the peripheral of droplet. On the other hand, concentric rings were observed at a high concentration of 0.8 mM CTAB with concentration of SDS below 6.4 mM SDS. Furthermore, solutions with a concentration of 0.8 mM CTAB and 1.6 mM SDS/6.4 mM SDS, there was no significant difference in the deposition behaviour on hydrophilic silicon wafer and hydrophobic ITO glass. It is interesting to note that at CTAB concentrations of 0.04 mM and 0.2 mM, fewer crystals were observed on the ITO glass substrate compared to the silicon wafer substrate. In the case of 0.8 mM CTAB with varying SDS concentration, an unexpected result was observed where 1.6 mM SDS had the highest initial contact angle, followed by 0.32 mM SDS. This observation suggests that CTAB played a more significant role in the initial contact angle than SDS did. Recommended future work could include exploring the effects of varying different concentrations of NaCl below the supersaturation concentration range (1-15% of NaCl) and varying different concentrations of surfactants at the critical micelle concentration (CMC) levels (1-1.5 CMC). This could potentially offer new insights into the evaporative and crystallisation behaviour of the droplets, as well as new deposition patterns.